CVD growth of monolayer WS2 through controlled growth temperature and time. (3rd July 2020) - Han, Jiangtao; Fang, Ruiqian; Zhu, Lei; Geng, Zhaoxin; He, Xunjun
Abstract: Recently, two-dimensional Transition metal dichalcogenides (TMDCs) have attracted widespread attention due to their unique electrical and optical properties. Specially, the monolayer WS2 has high photoluminescence intensity and short response time, and has high application potential in optoelectronic devices. Here, a method for synthesizing single-layer WS2 crystal by atmospheric pressure chemical vapor deposition (CVD) is reported. The triangular and regular hexagonal monolayer WS2 crystals are directly synthesized on Si/SiO2 substrate. Moreover, the measurement results show that the quality of the single-layer WS2 crystal can be further improved through adjusting the growth parameters, such as growth temperature and growth time.